Elastisitas Permintaan Rumah Sederhana Tipe 36 di Kota Padang Provinsi Sumatera Barat - Bunga Paramita (Bahtera Inovasi, 2021)
This research aims to analyze type 36 house demand elasticity in Padang City, West Sumatera Province. It used secondary data collected from 32 units of sample observation. The variables were 36-type housing price, distance to CBD, district density, number of household, and GDP per capita. The instruments of analysis were data panel regression using OLS approach, fixed effect , and random effect. The analysis results show that fixed method gives the best result of regression among the three approaches in the data panel. The variable of house price has a negative and significant correlation with the demand in Padang City with an elasticity level of 1.56%; the distance to CBD has a negative and correlation with demand with an elasticity level of 1.73%. The research results give a picture that the demand for simple houses in Padang city, West Sumatera Province is elastic toward the price of type 36 house, and distance to CBD.